Prescribing Pattern of Antibiotics in Neonatal Sepsis at Tertiary Teaching Hospital of Birgunj, Nepal - Smita, Singh; Parwez, Ahmad Md.; Ragni, Sinha; Prasad, Sarraf Deependra; Kumar, Singh Prabin (Med Phoenix, 2019)
Abstract with full text.